2023
DOI: 10.3390/en16104179
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Energy Efficiency in Additive Manufacturing: A Review and Framework for Future Research

Abstract: Additive manufacturing (AM) offers unique capabilities in terms of design freedom and customization, contributing to sustainable manufacturing. However, energy efficiency remains a challenge in the widespread adoption of AM processes. In this paper, we present a comprehensive review of the current research on energy efficiency in AM, addressing challenges, opportunities, and future directions. Our analysis reveals a lack of standardization in the measurement and reporting of energy consumption, making it diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 190 publications
0
3
0
Order By: Relevance
“…May and Psarommatis [95] explored maximizing energy efficiency in AM. Their research reveals that while the state of research on energy efficiency in AM is substantial, there is a lack of adequate research on sustainability.…”
Section: Future Prospects and Challenges In Am Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…May and Psarommatis [95] explored maximizing energy efficiency in AM. Their research reveals that while the state of research on energy efficiency in AM is substantial, there is a lack of adequate research on sustainability.…”
Section: Future Prospects and Challenges In Am Materialsmentioning
confidence: 99%
“…Some of the organizations that work on advancing the standards of AM include the International Organization for Standardization (ISO), under the ISO Technical Committee 261 (ISO TC/261), the American Society for Testing and Materials (ASTM International) under its ASTM F42 committee, the Society of Automotive Engineers (SAE), National Aeronautics and Space Administration (NASA), the American Welding Society (AWS), the National Aerospace and Defense Contractors Accreditation Program (NADCAP) [104], the India-based National Aerospace Laboratories (NAL), AFNOR (Association Française de Normalisation), AENOR (Asociación Española de Normalización y Certificación), VDI (Verein Deutscher Ingenieure), and DIN (Deutshe Industrie Normen) [105]. However, there is still a gap in standards and protocols for energy efficiency metrics in AM, in their work, May and Psarommatis analyzed current research on energy efficiency in AM and found that there is a lack of standards in measuring energy efficiency in AM [95].…”
Section: Initiatives and Standardsmentioning
confidence: 99%
“…Conventional manufacturing techniques often impose limitations on lightweight designs, but as mentioned earlier, AM has introduced unprecedented design freedom. New opportunities have arisen for the manufacturing and design of lightweight electric machines, which can enhance the efficiency and performance of these applications [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. This requirement is particularly critical in several industrial sectors that consume a significant portion of the total electricity, with electric motors and machinery accounting for at least 65% of this consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Its application has proven to reduce use of materials and optimize the final product, as well as presenting high deposition rate and lower equipment cost. [14,15]. The F42 American Society Committee for Testing and Materials (ASTM) defined AM as a process of joining materials to make objects from 3D model data, usually layer upon layer, as opposed to subtractive manufacturing methodologies, thus obtaining, in a first result, a geometry closer to the final result of the part [16,17,18].…”
Section: Introductionmentioning
confidence: 99%